Assessing the Homogeneity of Forage Mixtures Using an RGB Camera as Exemplified by Cattle Rations - Evgeniy A. Nikitin; Dmitriy Y. Pavkin; Andrey Yu. Izmailov; Alexander G. Aksenov (Applied Sciences, 2022)
The article examines existing methods for assessing the homogeneity of feed mixes in the feed industry and agriculture. As an alternative to existing approaches, the authors offer a low-cost online technology to assess the homogeneity of feed. The feedstuff under study includes feed mixes for cattle or compound feed consisting of naturally-grown feed (green mass of freshly cut grass, haylage, corn silage, etc.) and concentrated components (grain milling, sunflower, and soybean meal). The proposed method based on an RGB camera, a diode lamp, filters, and software is approved by a preliminary study of the physical properties of feed mix components by Specim IQ hyperspectral camera and revealing characteristics of light absorption of each type of components (concentrated/natural origin). The article presents a method of processing a feed mix image fixed by an RGB camera through light filters using Matlab Image Processing Toolbox tools, namely, a Color Thresholder app and Image Region Analyzer app.